2011
DOI: 10.1051/0004-6361/201117378
|View full text |Cite
|
Sign up to set email alerts
|

The subgiant branch ofω Centauri seen through high-resolution spectroscopy

Abstract: We analyze spectra of 18 stars belonging to the faintest subgiant branch in ω Centauri (the SGB-a), obtained with GIRAFFE@VLT at a resolution of R 17 000 and a S /N ratio between 25 and 50. We measure abundances of Al, Ba, Ca, Fe, Ni, Si, and Ti and we find that these stars have [Fe/H] = −0.73 ± 0.14 dex, similarly to the corresponding red giant branch population (the RGB-a). We also measure [α/Fe] = +0.40 ± 0.16 dex, and [Ba/Fe] = +0.87 ± 0.23 dex, in general agreement with past studies. It is very interestin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 76 publications
(215 reference statements)
1
14
0
Order By: Relevance
“…M 08, Yong & Grundahl 2008), in close analogy to what was observed in M 22 and ω Centauri (e.g. Marino et al 2009Marino et al , 2011Johnson & Pilachowski 2010;Pancino et al 2011). In contrast, Carretta et al (2011) claimed that the faint-SGB consists of barium-poor metal-poor stars while bright-SGB stars have an enhanced barium and iron abundance.…”
Section: The Chemical Composition Of the Double Rgb And Sgbsupporting
confidence: 74%
“…M 08, Yong & Grundahl 2008), in close analogy to what was observed in M 22 and ω Centauri (e.g. Marino et al 2009Marino et al , 2011Johnson & Pilachowski 2010;Pancino et al 2011). In contrast, Carretta et al (2011) claimed that the faint-SGB consists of barium-poor metal-poor stars while bright-SGB stars have an enhanced barium and iron abundance.…”
Section: The Chemical Composition Of the Double Rgb And Sgbsupporting
confidence: 74%
“…Option (b) may also be favoured by observations of rather uniform Al abundances in the SGB-a population (in our scenario the third generation, see Table 5) by Pancino et al (2011), suggesting that no anti-correlation is present in this sub-population. Although we have tried to resist the temptation in this paper to apply the Galactic plane passage gas purging model to other clusters we note that Carretta et al (2012) found that the anticorrelations involving Al, Mg, Na and O in NGC 6752 -another GC for which multiple populations possibly including large He-enrichements have been found -manifest themselves in a rather discrete fashion, in which different levels of enhancement and depletion cluster around discrete values that can be associated with individual sub-populations, rather than a continuous distribution that would be sugggested by a pure dilution mechanism.…”
Section: Discussionmentioning
confidence: 84%
“…SN II produce O and α-elements, but little Fe, while SN 1a produce mainly 56 Ni (which decays to form 56 Fe), and other isotopes of Ni in lower proportions, but not α-elements, so that [α/Fe] actually decreases (Iwamoto et al 1999, , their Table 3). SN 1a enrichment has been found in a few stars of the metal-rich "RGB-a" branch of ω Centauri (Pancino et al 2011). According to Marcolini et al (2007), SN 1a occur in small pockets of gas before being mixed with the interstellar medium, at variance with SN II, which pollute the interstellar medium uniformly.…”
Section: Origin Of the Enriched Gasmentioning
confidence: 99%